ANALISIS KESALAHAN SISWA MENYELESAIKAN SOAL CERITA BERDASARKAN KESADARAN METAKOGNISI - CANNY AUDIA NISA (Jurnal Edukasi dan Penelitian Matematika, 2018)
Word problems become an important part of mathematics, because they are used to apply formal knowledge and skills in real-world situations. In fact there are still many students who do mistakes when solving word problems. This study aims to determine the student errors of classVIII.2 of SMPN 4 Padang, who numbered 31 people in solving the word problem based on the level of metacognition awareness, and describing the factors that caused it. The type of research is descritive, namely describing students mistakes when completing a word problems. Data collection techniques used metacognition awareness inventory, word problem test, and interview quidelines. This study show students make mistakes in understanding problems, transformation errors, process skill errors, and encoding errors. Internal factors that cause students errors in solving word problems are 1) habits of students who do not repeat the lesson; 2) lack of attention of students to mathematics. While the external factors that cause student errors in solving story problem are 1) the influence of friends; 2) the teacher’s voice is slow with fast tempo when explaining the lesson; 3) schedule for math lesson in the afternoon.Keyword – analysis of student errors, newman error analysis, word problem, metacognition awareness